(untitled) (Metallurgy and Foundry Engineering, 2019)
The presented study performs an analysis of the effect of thermal treatment on the microstructure and corrosion resistance of the commercial prosthetic alloy Wironit ExtraHart (Co-Cr-Mo). Experiments of thermal treatment, homogenization, oversaturation as well as oversaturation with ageing of the alloys were carried out. Metallographic tests, hardness measurements, EDS analyses and electrochemical investigations were performed. For the examined samples, the corrosion potential (OCP) and polarization curve (LSV) were determined, based on which the corrosion properties in the simulated solution of artificial saliva were established. The results of the obtained tests made it possible to evaluate the effect of the performed thermal treatment on the changes in the properties (hardness) as well as the microstructure and corrosion resistance of the examined alloy Co-Cr-Mo.